2021
DOI: 10.1111/tpj.15355
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy‐related genes serve as heat shock protein 90 co‐chaperones in disease resistance against cassava bacterial blight

Abstract: SUMMARY Heat shock protein 90 (HSP90) is involved in plant growth and various stress responses via regulating protein homeostasis. Autophagy keeps cellular homeostasis by recycling the components of cellular cytoplasmic constituents. Although they have similar effects on cellular protein homeostasis, the direct association between HSP90 and autophagy signaling remains unclear in plants, especially in tropical crops. In this study, the correlation between HSP90 and autophagy signaling was systematically analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…In bread wheat, the ethylene‐responsive transcription factor ERF1 modulates pathogen‐triggered ROS accumulation and is involved in defense resistance to both the necrotrophic pathogen Rhizoctonia cerealis (Zhu et al., 2014) and the biotrophic pathogen powdery mildew (Liu et al., 2016). Here, ethylene and the ethylene‐responsive MeEIL5 increased flg22‐induced ROS burst to confer improved immunity, which was consistent with the results of other positive disease regulators (MeHSP90.9 and MeRAV5) in cassava (Wei et al., 2021b; Yan et al., 2021). In addition, overexpression of MeEIL5 or MeASMT2 or melatonin alleviated 1‐MCP‐mediated disease susceptibility and ROS burst, further indicating that MeEIL5 ‐integrated MeASMT2 transcript and melatonin accumulation underlie the ethylene‐improved immune response.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In bread wheat, the ethylene‐responsive transcription factor ERF1 modulates pathogen‐triggered ROS accumulation and is involved in defense resistance to both the necrotrophic pathogen Rhizoctonia cerealis (Zhu et al., 2014) and the biotrophic pathogen powdery mildew (Liu et al., 2016). Here, ethylene and the ethylene‐responsive MeEIL5 increased flg22‐induced ROS burst to confer improved immunity, which was consistent with the results of other positive disease regulators (MeHSP90.9 and MeRAV5) in cassava (Wei et al., 2021b; Yan et al., 2021). In addition, overexpression of MeEIL5 or MeASMT2 or melatonin alleviated 1‐MCP‐mediated disease susceptibility and ROS burst, further indicating that MeEIL5 ‐integrated MeASMT2 transcript and melatonin accumulation underlie the ethylene‐improved immune response.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, we revealed the essential role of melatonin biosynthesis in disease resistance to CBB in cassava (Wei et al, 2017). In addition, we also highlighted the crucial modulation of heat shock protein 90 (HSP90) in plant immunity through modulation of melatonin, SA, and auxin signaling and autophagy in cassava (Wei et al, 2021b;Wei et al, 2021a). However, the molecular pathways of immune responses in cassava remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial growth assay showed that Xam11 populations in the four mutant lines were significantly smaller than that in the wild type at 3 dpi and 7 dpi (Figure 1I). Callose is deposited on the cassava cell wall during the early stages of Xam pathogen attack which restricts pathogen growth (Wei et al ., 2021). The leaves of the mutant cassava lines displayed significantly more callose depositions at 3 dpi than that in the wild type (Figure 1J).…”
Section: Figurementioning
confidence: 99%